TINJAUAN PENGGUNAAN ANTIPSIKOTIK PADA PENGOBATAN SKIZOFRENIA DI RUMAH SAKIT PROF. DR. V. L. RATUMBUYSANG MANADO PERIODE JANUARI 2013-MARET 2013 - Jarut, Yulia Maria; Fatimawali, Fatimawali; Wiyono, Weny I (PHARMACON, 2013)
ABSTRACTSchizophrenia is one of psychiatric disorders that caused by brain damage. The prevalence ofSchizophrenia patients in North Sulawesi were 2,4%. One way of Schizophrenia handling isgiving antipsychotics to prevent the symptoms. The aim of this research is to analyze the useof Antipsychotics on Schizophrenia patient which treated at Ratumbuysang Manado Hospital.This research is survey description research with data sampling by retrospective. Thisresearch were conducted to 142 medical records of patients period January 2013 to March2013 which receive Antipsychotics medication. Data were analyzed by univariate analysis(descriptive). Obtained data shows that the most single therapy of Antipsychotics isrisperidon (21,1%), and combined therapy was haloperidol and chlorpromazine (23,2%). Themost treatment category of Schizophrenia is the typical antipsychotic treatment (41,5%).Keywords : Schizophrenia, Antipsychotics, brain damage